2020
DOI: 10.3390/ijerph17114022
|View full text |Cite
|
Sign up to set email alerts
|

Social Participation in Relation to Technology Use and Social Deprivation: A Mixed Methods Study Among Older People with and without Dementia

Abstract: Social participation is a modifiable determinant for health and wellbeing among older people; however, social participation is increasingly dependent on technology use. This study investigated social participation in relation to Everyday Technology use and social deprivation of the living environment, among older people with and without dementia in the United Kingdom. Sixty-four people with dementia and sixty-four people without dementia were interviewed using standardized questionnaires: The Participation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…In the total sample, the use of more ET was at a medium level (r s ¼0.41) significantly correlated to a higher number of places visited. These results confirm, in similarity to studies of older people with cognitive impairments [5,38,39], the importance of the use of ET for out-of-home participation. Consequently, it can be argued from a justice perspective [3,4] that recognizing ET in and related to public space is important in providing equal opportunities for daily activities and participation in the digitalized society.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the total sample, the use of more ET was at a medium level (r s ¼0.41) significantly correlated to a higher number of places visited. These results confirm, in similarity to studies of older people with cognitive impairments [5,38,39], the importance of the use of ET for out-of-home participation. Consequently, it can be argued from a justice perspective [3,4] that recognizing ET in and related to public space is important in providing equal opportunities for daily activities and participation in the digitalized society.…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, particularly participants in the MD/SD group may face unequal possibilities to out-of-home participation or injustices [13] due to the design of the society and societal services. This implies, similarly with previous research of people with ABI in working age [40] and of older persons with cognitive impairment [5, 39,41], that the relationship between ET use and visits to places outside the home only is evident in those with difficulties in the use of ET or in those using fewer ETs. Research has also showed that the GR group has an ability to use ET that is on level with healthy controls [22,40].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…According to Dröes et al [ 89 ], personal and disease-related factors, social environment factors, and physical environment factors can impede or enhance their social participation. Similarly, the findings of Gaber et al [ 90 ] suggest that contextual factors, such as characteristics of the physical and social environment, need to be considered when enhancing the social participation of people living with dementia. Further research should focus on identifying factors of technological interventions that facilitate social participation in older adults and, particularly, in older adults with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…The decision-making process, which follows a strong emotional experience that has been seen by the teachers individually and collectively involved in the group activity, will also be monitored. This study aims to add value to the themes already developed, as it builds on the 2.0 evolution of DST and experiments with this practice within the online teaching field and in the initial training of teachers [23]. The examination of DST, which was launched in recent years, can be enriched through the inclusion of cognitive and social psychology components linked to participation and the construction of learning communities.…”
Section: Introductionmentioning
confidence: 99%